Luck, Choice and Responsibility: An Experimental Study of Fairness Views - Johanna Möllerström; Bjørn-Atle Reme; Eric Ø. Sørensen (Research Institute of Industrial Economics (IFN), 2014)
We conduct a laboratory experiment where third-party spectators can redistribute resources between two agents, thereby offsetting the consequences of controllable and uncontrollable luck. Some spectators go to the limits and equalize all or no inequalities, but many follow an interior allocation rule previously unaccounted for by the fairness views in the literature. These interior allocators regard an agent's choice as more important than the cause of her low income and do not always compensate bad uncontrollable luck. Instead, they condition such compensation on the agent's decision regarding controllable luck exposure, even though the two types of luck are independent.
Keywords: C91; D63; D81; H23; 330; Fairness; Responsibility; Option luck; Brute luck; Experiment